Evaluating the Accuracy of BMP280 and BME280 Sensors for Sea Level in a Coastal Environment: A Field Study at Tanjung Siambang Pier - Hollanda Arief Kusuma; Yuliani Yuliani; Tonny Suhendra; Dhanushka Devendra; Dwi Eny Djoko Setyono (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Monitoring sea level is important for assessing climate change impacts, coastal management, and predicting hazards. Accurate measurements of air pressure is essential for precise sea level monitoring through pressure-to-altitude conversion. Additionally, understanding tidal patterns and their dominant components is crucial for comprehensive sea level analysis. This research aimed to investigate the accuracy of BMP280 and BME280 sensors in measuring air pressure and altitude to monitor sea level. Comparing air pressure data from the BMP280, BME280, and BMKG sensors showed that the BMP280 sensor had a higher accuracy than the BME280 sensor. Linear regression was used to decrease the error value. After calibration, BME280 and BMP280 did not differ with the BMKG sensor using one-way ANOVA and Tukey test. A field test was also conducted to assess the ability of the BMP280 sensor to measure sea level height from air pressure conversion. It was found that the BMP280 sensor could not provide an accurate sea level height value with an R² value of 0.00931. A Fourier analysis was used to investigate the tidal pattern in Tanjung Siambang using six constituents, symbols S1, O2, M2, S2, S4, and S6, with periods of 24, 12.91, 12.42, 12, 6, and 4 h. It revealed that the dominant components were M2 and S2, caused by the moon's and the earth's gravitational pull. This study highlights the limitations of the BMP280 sensor in providing accurate sea level height measurements and the importance of the M2 and S2 tidal components in determining sea tides in Tanjung Siambang.